The Shift Analysis in Transparency and Accountability Degrees on Regional Financial Management - Rohma, Frida Fanani (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2024)
Accrual-based accounting is an attempt by the International Public Sector Accounting Standards Board (IPSASB) to increase transparency and accountability. As it develops, the ability of accrual-based accounting to increase transparency and accountability is still questionable. This research uses a literature review under charting the field technique analysis of the evolution of transparency and accountability transition of the accrual basis application from the perspective of costs and benefits. The study shows that the gap between conceptual framework and empirical research indicates the non-optimal accrual-based accounting in promoting transparency and accountability. The development of accrual-based accounting is in line with increased transparency and accountability; however, it is followed by earnings management practices that still need to be considered. Therefore, primary usage must be improved by improving an adequate audit system.Keywords: Accountability, Accrual Based Accounting, Earnings Management, Financial Statements, Transparency